Eficiência financeira das distribuidoras de energia no período de 2011 a 2014: Uma análise comparativa usando DEA - Fabrício Eduardo Jacob; Gabriel Godofredo Fiuza de Bragança (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This paper uses Data Envelopment Analysis (DEA) to evaluate the financial sustainability of the Brazilian electricity distributors taking into account financial statements, regulatory and quality information in the period between 2011 and 2014. It also analyzes characteristics of the companies such as size, private or state ownership and controlling group. The results show that while Elektro, Coelba, Mux Energia and CPFL Paulista are benchmarks in most indicators, the majority of the other firms presents poor performances when compared to them. The finds also indicate that whether scale is not an important financial performance determinant, state owned companies had critically worse indicators than their private peers.
Keywords: C61; G31; L94; 330; Distribution of electricity; economic and financial efficiency; DEA